Immunologic benefits of maternal living donor allografts in pediatric liver transplantation: fewer rejection episodes and no evidence of de novo allosensitization. (21st November 2021) - Barbetta, Arianna; Meeberg, Glenda; Rocque, Brittany; Barhouma, Sarah; Weaver, Carly; Gilmour, Susan; Faytrouni, Farah; Guttman, Orlee; Zielsdorf, Shannon; Etesami, Kambiz; Kwon, Yong; Yanni, George; et al.
Abstract: Background: Pediatric liver transplant (LT) recipients of maternal living liver donor (LLD) grafts have been reported to experience fewer rejection episodes. However, it is unclear whether this benefit translates to reduction in developing donor‐specific antibody (DSA) among maternal‐LLD recipients. The aim of this study was to compare immunologic outcomes among maternal‐LLD, non‐maternal‐LLD, and deceased donor liver transplant (DDLT) recipients. Methods: Children (≤18 years) who underwent LT between 1/1998 and 12/2019 at two high‐volume LT centers in North America were evaluated. Patients were divided into three groups by type of graft received (maternal‐LLD, non‐maternal LLD, and DDLT). Clinical variables and outcomes were compared according to each graft type. Results: A total of 450 pediatric primary LT were analyzed: 275 (61.1%) DDLT, 73 (16.2%) maternal‐LLD, and 102 (22.6%) non‐maternal‐LLD. Children receiving LLD grafts were less likely to develop rejection when compared to the DDLT group (DDLT 46.9% vs. maternal‐LLD 31.5% vs. non‐maternal‐LLD 28.4%, p  = 0.001). There was no difference in rejection rates between maternal and non‐maternal‐LLD recipients. A higher percentage of maternal‐LLD recipients were on immunosuppression monotherapy compared to non‐maternal‐LLD and DDLT recipients (6.7% vs. 1.2 vs. 2.4%, respectively). A subgroup of 68 patients were tested for DSA post‐LT. Maternal‐LLD recipients were less likely to develop de novo DSA (maternal‐LLD 11.8% vs. non‐maternal‐LLD 19.3% vs. DDLT 43%, p  = 0.018). None of the maternal‐LLD recipients developed antibody‐mediated rejection. Conclusions: These data support the concept of immunologic benefit of maternal‐LLD in pediatric LT, with lower rates of rejection and allosensitization post‐LT when compared to DDLT recipients.